Nurses in France: Between Autonomy and Subordination in Front Line Care. (14th May 2015) - Jovic, Ljiljana; Bianchi, Evelyne; Decouflet, Sylvie; Loizeau, Valérie; Amiot, Patricia; Teixeira, Maria
In France, medical practitioners are aware that the practice of the delivery of primary care by nurses occurs in other countries. However, there is disagreement about how to implement this practice. This aspect of the issue of front line care has not yet been studied in France. In this article, our aim is to identify to what extent the delivery of primary care by nurses is considered acceptable by doctors and nurses working in hospital emergency departments and in public and private health centers. The results of our research provide a picture of opinions that exist among doctors and nurses. These opinions highlight practices that are outside the current regulations and present perspectives, which range from conditionally in favor to unfavorable. Such opinions contribute to our knowledge because they are derived from the professionals directly involved and describe what is acceptable in this particular context.